An inverse problem approach to stiffness mapping for early detection of breast cancer: tissue phantom experiments. Issue 7 (3rd July 2019) - Olson, Lorraine G.; Throne, Robert D.; Nolte, Adam J.; Crump, Allison; Griffin, Kaelyn; Han, Tianhong; Iovanac, Nicolae; Janssen, Thomas; Jones, Michael; Ling, Xiaoyin; Samp, Michael
ABSTRACT: Early detection of breast cancer will continue to be crucial in improving patient survival rates. Our ultimate goal is to develop an electro-mechanical device to automate and refine the manual breast exam process, and use inverse techniques to generate a tissue stiffness map of the breast tissue. We have previously presented computational simulations of the stiffness mapping approach, which employs static indentations of the tissue and measurements of surface displacements. In this paper, we report on experimental validation of the technique with tissue phantom experiments. We tested 12 tissue phantom samples without simulated tumours and 14 tissue phantom samples with simulated tumours. Our stiffness mapping approach correctly identified all 26 samples.